Efektivitas Model Cooperative Learning Tipe Group Investigation Berbantuan Qr Code (Quick Response Code) dalam Meningkatkan Hasil Belajar Siswa: Penelitian - Anandita Putri Salsabila; Retno Mustika Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Developed countries are always accompanied by high-quality education. This study aims to determine the learning outcomes of students from the application of the cooperative learning model type Group Investigation (GI). This study was conducted in class X of SMA Semen Gresik of 28 students. The research method used in this study was a quasi-experimental design with a nonequivalent control group design, utilizing IBM SPSS software version 27. The results of the independent sample t-test yielded a value of 0.039. This means that there is a significant difference between the learning outcomes of the experimental class using the GI model and the control class using the jigsaw model. Regarding the effectiveness of the GI model, it was proven to be effective in improving student learning outcomes. This was assessed based on the N gain percentage of the experimental class, which was 78,24%. Therefore, teachers can use this combination of learning models and media by considering student learning motivation, time, and adequate learning resources